Only a subset of the binary cell fate decisions mediated by Numb/Notch signaling in Drosophila sensory organ lineage requires Suppressor of Hairless. - Wang, S.; Younger-Shepherd, S.; Jan, L.Y.; Jan, Y.N. (Development, 1997)
In Drosophila, an adult external sensory organ (bristle) consists of four distinct cells which arise from a sensory organ precursor cell via two rounds of asymmetric divisions. The sensory organ precursor cell first divides to generate two secondary precursor cells, IIa and IIb. The IIa cell then divides to produce the hair cell and the socket cell. Shortly after, the IIb cell divides to generate the neuron and the sheath cell. The membrane-associated protein Numb has been shown to be required for the first two asymmetric divisions. We now report that a new hypomorphic numb mutant not only displays a double-socket phenotype, due to a hair cell to socket cell transformation, but also a double-sheath phenotype, due to a neuron to sheath cell transformation. This provides direct evidence that numb functions in the neuron/sheath cell lineage as well. Those results, together with our observation from immunofluorescence analysis that Numb forms a crescent in the dividing IIa and IIb cells suggest that asymmetric localization of Numb is important for the cell fate determination in all three asymmetric cell divisions in the sensory organ lineage. Interestingly, we found that in the hair/socket cell lineage but not the neuron/sheath cell lineage, a Suppressor of Hairless mutation acts as a dominant suppressor of numb mutations whereas Hairless mutations act as enhancers of numb. Moreover, epistasis analysis indicates that Suppressor of Hairless acts downstream of numb, and results from in vitro binding analysis suggest that the genetic interaction between numb and Hairless may occur through direct protein-protein interaction. These studies reveal that Suppressor of Hairless is required for only a subset of the asymmetric divisions that depend on the function of numb and Notch.